2020
DOI: 10.21203/rs.3.rs-37088/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two infants with COVID-19 acquired from infected mothers: The incompatibility of maternal intensity and infant lung involvement: A case report

Abstract: IntroductionThe outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was declared a public health emergency by world health organization (WHO) on 30 January 2020. Recent studies have suggested that infants present the symptoms of COVID-19. Although the presentation of the disease in babies is variable, there are limited studies about the infected babies with 2019-nCoV.Case presentationIn this study, we have presented a case report of two infants with COVID-19. According to the simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In a study by Moeindarbary et al, researchers reported infants with coronavirus infection and that they had worse clinical condition than their mothers. The severity of pneumonia and the degree of lung involvement in these infants were not related to the stage and severity of the disease in infected mothers [21]. Chen et al's study in Wuhan also reported vertical transmission between pregnant women with COVID-19 and their infants [22].…”
Section: Discussionmentioning
confidence: 87%
“…In a study by Moeindarbary et al, researchers reported infants with coronavirus infection and that they had worse clinical condition than their mothers. The severity of pneumonia and the degree of lung involvement in these infants were not related to the stage and severity of the disease in infected mothers [21]. Chen et al's study in Wuhan also reported vertical transmission between pregnant women with COVID-19 and their infants [22].…”
Section: Discussionmentioning
confidence: 87%